2021
DOI: 10.3390/ma14040826
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Mechanical Properties of Cr2AlC MAX Phase Coatings on TiBw/Ti6Al4V Composite Prepared by HiPIMS

Abstract: The high-power impulse magnetron sputtering (HiPIMS) technique is widely used owing to the high degree of ionization and the ability to synthesize high-quality coatings with a dense structure and smooth morphology. However, limited efforts have been made in the deposition of MAX phase coatings through HiPIMS compared with direct current magnetron sputtering (DCMS), and tailoring of the coatings’ properties by process parameters such as pulse width and frequency is lacking. In this study, the Cr2AlC MAX phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…The MAX phase materials are able to attract great attention owing to their exceptional performance combining both ceramics (elastically rigid, lightweight, creep and fatigue resistant as ceramic materials) and metals (machinable, electrically and thermally conductive, not susceptible to thermal shock, plastic at high temperature and exceptionally damage-tolerant) [1,2]; consequently, they are promising candidates such as in high-temperature technology as components, sliding electrical contacts, and contacts for 2D electronic circuits, Li-ion batteries, wear and corrosion-resistant coatings, superconducting materials, spintronics, and nuclear industry. [2,[5][6][7][8][9][10]The hybrid properties of MAX phases are due to strong covalent M-X bonds and relatively weak metallic M-A bonds within their structure [2,11,12]. These challenging properties are always motivating scientists; consequently, more than 150 MAX phases have been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The MAX phase materials are able to attract great attention owing to their exceptional performance combining both ceramics (elastically rigid, lightweight, creep and fatigue resistant as ceramic materials) and metals (machinable, electrically and thermally conductive, not susceptible to thermal shock, plastic at high temperature and exceptionally damage-tolerant) [1,2]; consequently, they are promising candidates such as in high-temperature technology as components, sliding electrical contacts, and contacts for 2D electronic circuits, Li-ion batteries, wear and corrosion-resistant coatings, superconducting materials, spintronics, and nuclear industry. [2,[5][6][7][8][9][10]The hybrid properties of MAX phases are due to strong covalent M-X bonds and relatively weak metallic M-A bonds within their structure [2,11,12]. These challenging properties are always motivating scientists; consequently, more than 150 MAX phases have been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Arc evaporation is a high ionization technique that utilizes a low-voltage, high-current arc to melt and vaporize the target material, which then condenses on the substrate, forming a dense and hard coating with strong adhesion properties. A potential downside is the production of microdroplets, which can roughen the coating's surface [19][20][21] and must be removed during the post-treatment of the surface. In this study, the TiN arc coating was deposited through arc evaporation using high purity Ti targets evaporated in an N 2 atmosphere.…”
Section: Coating Deposition and Characterizationmentioning
confidence: 99%
“…Conversely, HiPIMS is renowned for its ability to produce inherently smoother coatings with superior density and corrosion resistance, which are key traits for the longevity of orthopedic implants [18]. The advancements in HiPIMS technology, especially in the deposition of CrN/NbN and Cr2AlC MAX phase coatings, indicate its capacity to meet and exceed load requirements while reducing metal ion release [19,20]. Additionally, the exploration of HiPIMS W-C and W-C:H coatings in tribological applications suggests the potential for achieving superlubricity under certain conditions, a testament to its suitability for orthopedic applications [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Changing the power of the magnetron sputtering can also affect the substructural properties of the coatings. In [39], a comparative study of Cr 2 AlC coatings deposited at different average HiPIMS powers was performed, where the effect of pulse duration (20…60 μs) was found to be more effective than frequency (1.2…1.6 kHz). The results of the study showed that increasing the power in the range of 110…440 W increased the deposition rate of amorphous layers by 3.5 times.…”
Section: Influence Of Pvd Deposition Parameters On the Structure Of M...mentioning
confidence: 99%